Social desirability and mentorship influencing new venture creation by women entrepreneurs in India - Choudhary, Jyoti; Hashim, Haslinda; Ho, Jo Ann; Sambasivan, Murali (Human Resource Management Academic Research Society, 2020)
Women entrepreneurs in developing countries like India find opportunity recognition challenging thereby, preventing them from creating new ventures, particularly SMEs. Social desirability and mentorship have been recognised an important dimension of social support for women entrepreneurs. Environments, where the social desirability of women entrepreneurship is higher, can encourage entrepreneurship as a career path for women. Similarly, external knowledge provided by experienced mentor can be one of the most relevant sources of information for women to recognise opportunities and exploit it by creating new ventures. Mentorship becomes more important for women considering they have less networks, awareness and social capital. However, little knowledge has been advanced to investigate their influence on mentorship and social desirability opportunity recognition and creation of women owned SMEs in India. Presence of these support factors can encourage women entrepreneurship whereas lack of them can discourage women to pursue entrepreneurship. Furthermore, there is a dearth of studies examining the mediating role of opportunity recognition between social desirability, mentorship and venture creation. Based on the synthesis of vast amount of prior literature, a conceptual model of venture creation is developed to explain the relationships amongst the constructs under study. Consequently, testable propositions are proposed for future empirical examinations. The proposed relationships are further explained with the support of Institutional theory and Resource based theory.